2020
DOI: 10.1186/s12955-020-01370-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of type 1 diabetes on young adults’ health-related quality of life

Abstract: Background: Young adulthood is a challenging period for people with diabetes mellitus type 1 (T1DM) as they are facing multiple life transitions while managing a demanding disease. This poses a risk for impaired health-related quality of life (HRQOL). We assessed HRQOL in a cohort of young adults with T1DM in the Netherlands, and compared outcomes with those of Dutch norm groups of healthy young adults and young adults with a chronic disease. Methods: We analyzed data collected in a larger evaluation study on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
0
26
0
1
Order By: Relevance
“…Average household income and treatment modality were not strong predictors of differences in QoL. Other studies have shown an association between a lower QoL and factors like poor glycemic control, fear of hypoglycemia and complications, and lack of confidence in self-management (Alvarado-Martel et al, 2015;Liu et al, 2020) being higher in FD users. This suggests that a subsidized alternative of MDI could improve QoL, decreasing cardiovascular disease probability by 30% and acute cardiovascular events by 32% (DCCT, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…Average household income and treatment modality were not strong predictors of differences in QoL. Other studies have shown an association between a lower QoL and factors like poor glycemic control, fear of hypoglycemia and complications, and lack of confidence in self-management (Alvarado-Martel et al, 2015;Liu et al, 2020) being higher in FD users. This suggests that a subsidized alternative of MDI could improve QoL, decreasing cardiovascular disease probability by 30% and acute cardiovascular events by 32% (DCCT, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…An example is the structural use of quality of life questionnaires. Regularly addressing psychosocial issues is highly recommended for young adults with T1DM, many of whom experience psychosocial problems and diabetes-related distress (Bronner et al, 2020;Iyengar et al, 2019;Van Staa et al, 2020). However, we do not know if and how the teams that use quality of life questionnaires bring up quality of life issues during consultations.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the structural use of quality of life questionnaires. Regularly addressing psychosocial issues is highly recommended for young adults with T1DM, many of whom experience psychosocial problems and diabetes-related distress [7,25,32]. However, we do not know if and how the teams that use quality of life questionnaires bring up quality of life issues during consultations.…”
Section: Comparisons With Existing Literaturementioning
confidence: 99%